Hypertension Patients' Perceptions of Healthy Lifestyles and Complications of Hypertension - Mahensa, Noval Gentha; Ichsan, Burhannuddin; Lestari, Nining; Soekiswati, Siti (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to identify patient perceptions, influencing factors, patient efforts, and increasing compliance with healthy lifestyles in hypertensive patients. Methodology: This study uses a qualitative approach method with a phenomenological design to explore in-depth information based on patient knowledge and understanding. The study was conducted on hypertensive patients from October to November 2024 at the Gatak Health Center. Results: Each patient has the same perception and knowledge about hypertension, but differs in the implementation of a healthy lifestyle and knowledge about complications of hypertension. Most patients agree that hypertension is dangerous and requires the implementation of a good lifestyle to prevent the development of hypertension, but some patients think that hypertension is not dangerous as long as they implement a good and correct healthy lifestyle. If this is put together, it will become the same core, only different in understanding, it is natural that this happens because each patient has a different mindset and understanding. All patients have learned information about hypertension from medical personnel education, television broadcasts, and personal experiences with the motivation of wanting to recover from hypertension. Applications/Originality/Value: Exploring how patients themselves perceive and understand these steps. Knowing the patient's perception will help in designing an educational program that is more targeted and in accordance with their needs and understanding.